(3GdfXGe GdbGfhfj ddeTJbGJ GdeGdjI aj Shb GdChQGb GdeGdjI (B: s (3OQGSI ebGQfI (B/ s - (3eMeO UHQj GdSYOGhj s; (3SGej YHOGdHGbj CHhUGdM (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2015)
(3HOCJ GdOQGSI HebOeI YGeI JegjOG dehVhY GdHMK JfGhdJ CgejI GdOQGSI hGdgOa efgG(B: (3ceG JfGhdJ efgL GdHMK aj GdOQGSI(B: (3hbO bSeJ GdOQGSI Edi aUd JegjOj(B: (3hHGH Chd JfGhd JfXje GdeTJbGJ GdeGdjI YeheG(B: (3hHGH KGf JfGhd Cge YbhO GdeTJbGJ GdeGdjI hgj GdGNJjGQGJ(B: (3GdeSJbHdjGJ(B: (3GdeHGOdGJ(B: (3hNGJeI(B: (3hbGFeI HGdeUGOQ hGdeQGLY(B. (3hjhGLg GdeJYGedhf aj GdCShGb GdeGdjI YOe GdJCcO(B: (3Ch GdNWQ(B: (3Ch GdZQQ aj JYGedGJge(B: (3hGdfGJLI Yf YOe JhaQ GdeYdheGJ dLejY GdeJYGedjf HGdJSGhj(B: (3acGf GddLhA Edi GdeTJbGJ GdeGdjI(B: (3hgj YHGQI Yf YbhO jLQj JShjJgG aj JGQjN eSJbHdj(B: (3dgG JcdaI VFjdI ebGQfI HeRGjGgG Ydi GdeJYGedjf aj GdShb GdeGdjI NGUI GdeJMhWjf(B: (3hHTcd YGe jecf Gdbhd Cf GdJYGed Ydi GdeTJbGJ GdeGdjI SGge aj JLGhR GdbhGYO GdJfWjejI GdJbdjOjI ddfTGW GdeGdj(B: (3hCfg ef YhGed GdJMOjK aj GdGhQGb GdeGdjI(B: (3GdJj JDOj Edi RjGOI GdJhLg Edi GdGSJKeGQ HTcd YGe hGdJMajR Edjgs
(3CWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI, (B2015s
(3HHdjhLQGajG(B: (3UaMGJ (B-451: 476.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdfXGe GdbGfhfj dShb GdChQGb GdeGdjIs; (3JOGhd GdChQGb GdeGdjIs; (3EWGQ GdeTJbGJ GdeGdjIs; (3GdJMhWs; (3EOGQI GdeNGWQs; (3GdeVGQHIs; (3YbO GdGNJjGQs; (3GdYbO GdeSJbHdj s; (3GdeHOGdGJ s; (3GdebGjVGJs; (3GdfXGe GdbGfhfj dShb GdChQGb GdeGdjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- 2015